Identifikasi Aspek Dominan Illness perception pada Pasien Diabetic Foot Ulcer - Cynthia Eka Fayuning Tjomiadi; Onieqie Ayu Dhea Manto (Unit Penelitian dan Pengabdian Kepada Masyarakat, STIKES Dirgahayu Samarinda, 2022)
Abstract Background: Diabetic Foot Ulcer (DFU) is a microvascular complication in diabetes mellitus which allows it to be prevented through multidisciplinary collaboration that involves the active participation of patients, namely the application of self-care behavior. But unfortunately self-care behavior itself is still relatively low. Many studies have identified the relationship between knowledge and behavior to prevent LKD, but knowledge is not the only factor that influences this. Illness perceptions is a person's point of view that plays an important role in behavior and decision making. So, it is necessary to identify the dominant aspects of illness perceptions in DFU patients. Objective: This study aims to identify the dominant aspects of illness perceptions on LKD patients. Methods: This research design uses a descriptive quantitative method with data collection through a questionnaire survey. Results: This study used 43 samples after being identified there were 2 dominant aspects of illness perception in LKD patients, namely aspects of treatment control and coherence. Conclusion: The higher the patient's confidence in the treatment control and understanding of the disease, the better the foot care will be. Keywords: Diabetic Foot Ulcer, Dominant aspect, illness perceptions